Epidemiological Survey of Enterovirus Infections in Taiwan From 2011 to 2020: Retrospective Study - Fang-Chen Liu; Bao-Chung Chen; Yao-Ching Huang; Shi-Hao Huang; Ren Jei Chung; Pi-Ching Yu; Chia-Peng Yu (JMIR Publications, 2024)
Abstract BackgroundYoung children are susceptible to enterovirus (EV) infections, which cause significant morbidity in this age group. ObjectiveThis study investigated the characteristics of virus strains and the epidemiology of EVs circulating among young children in Taiwan from 2011 to 2020. MethodsChildren diagnosed with EV infections from 2011 to 2020 were identified from the routine national health insurance data monitoring disease system, real-time outbreak and disease surveillance system, national laboratory surveillance system, and Statistics of Communicable Diseases and Surveillance Report, a data set (secondary data) of the Taiwan Centers for Disease and Control. Four primary outcomes were identified: epidemic features, characteristics of sporadic and cluster cases of EV infections, and main cluster institutions. ResultsFrom 2011 to 2020, between 10 and 7600 person-times visited the hospitals for EV infections on an outpatient basis daily. Based on 2011 to 2020 emergency department EV infection surveillance data, the permillage of EV visits throughout the year ranged from 0.07‰ and 25.45‰. After typing by immunofluorescence assays, the dominant type was coxsackie A virus (CVA; 8844/12,829, 68.9%), with most constituting types CVA10 (n=2972), CVA2 (n=1404), CVA6 (n=1308), CVA4 (n=1243), CVA16 (n=875), and CVA5 (n=680); coxsackie B virus CVB (n=819); echovirus (n=508); EV-A71 (n=1694); and EV-D68 (n=10). There were statistically significant differences (P ConclusionThis study is the first report of sporadic and cluster cases of EV infections from surveillance data (Taiwan Centers for Disease and Control, 2011‐2020). This information will be useful for policy makers and clinical experts to direct prevention and control activities to EV infections that cause the most severe illness and greatest burden to the Taiwanese.